2016
DOI: 10.1097/mao.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Outer Hair Cell Molecular Protein, Prestin, as a Serum Biomarker for Hearing Loss

Abstract: This work, for the first time, provides proof of concept that an otologic serum biomarker level can change after acoustic trauma and hearing loss. Our approach represents an entirely novel strategy in hearing diagnostics and has both research and clinical potential. Further work is needed to map out the temporal course of change in serum prestin concentrations after inner ear trauma, better define the relationship of serological and functional changes, and explore application to other etiologies of hearing los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…Highly specialized inner ear functions are made possible by unique proteins which upon disruption of function or cellular injury may be released into circulation where they could provide useful information. Specifically, we have proposed otolin-1 2 and prestin 12 as a serological biomarkers and provided proof of concept in BPPV 2 and noise-induced hearing loss 13 , respectively. Paving the path to practical application of inner ear biomarkers, however, requires additional validation.…”
Section: Discussionmentioning
confidence: 98%
“…Highly specialized inner ear functions are made possible by unique proteins which upon disruption of function or cellular injury may be released into circulation where they could provide useful information. Specifically, we have proposed otolin-1 2 and prestin 12 as a serological biomarkers and provided proof of concept in BPPV 2 and noise-induced hearing loss 13 , respectively. Paving the path to practical application of inner ear biomarkers, however, requires additional validation.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, 2 weeks after noise trauma when there are missing OHCs in the cochlea, we have demonstrated decreased prestin levels relative to controls. 5 We only evaluated cisplatin at 8 mg/kg, but varying doses of cisplatin would likely accelerate or decelerate the rate of OHC damage and thus, prestin levels relative to baseline based on the rate of OHC damage. Alternatively, prestin levels may have remained elevated above the baseline due to a temporary elevation of prestin gene expression in the remaining OHCs that maintains circulatory prestin levels near baseline.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 We extended this concept to sensorineural hearing loss and noise-induced hearing loss through measurement of the outer-hair cell-specific protein, prestin, in circulation. 4,5 In order for the concept of otologic biomarkers to be adopted into clinical practice, validation in other experimental settings, such as ototoxicity, is necessary. In addition, it should be demonstrated that biomarker levels are sensitive to interventions aimed at ameliorating otologic damage.…”
mentioning
confidence: 99%
“…Other factors, including prestin, anti-prestin autoantibodies, and coenzyme Q10, may be prognostic in patients with SSNHL. Prestin, an outer hair cell (OHC)-specific protein, has been reported to be a biochemical marker for early diagnosis of SNHL loss in an animal model of noise-induced hearing loss and cisplatin ototoxicity [ 58 , 59 ]. Prestin concentration in serum, as measured by ELISA, was reported to be significantly higher in ISSHL patients than in normal controls ( p < 0.001).…”
Section: Biomarkers In Ssnhlmentioning
confidence: 99%